Training Shoes do not Decrease the Negative Work of the Lower Extremity Joints - Hashizume, Satoru; Murai, Akihiko; Hobara, Hiroaki; Kobayashi, Yoshiyuki; Tada, Mitsunori; Mochimaru, Masaaki (International Journal of Sports Medicine, 2017)
Different types of running shoes may have different influence on the negative work of each lower extremity joint. Clarifying this influence can reduce the potential risk of muscle injury. The present study examined the difference in the negative work and associated kinetic and kinematic parameters of the lower extremity joints between training shoes and racing flats during the contact phase of running. Participants were asked to run on a runway at a speed of 3.0 m·s-1 for both training shoes and racing flats. The negative work and associated kinetic and kinematic parameters of each lower extremity joint were calculated. No difference was found in the negative work of the hip and ankle joints between the two types of running shoes. Meanwhile, the negative work of the knee joint was significantly greater for training shoes than for racing flats. This aspect was related to a longer duration of the negative power of the knee joint with the invariant amplitude of the negative power, moment, and angular velocity. These results suggest a higher potential risk of muscle injury around the knee joint for training shoes than for racing flats.
Keywords: running shoes; musculoskeletal injury; muscle contraction; kinematics; kinetics